MiR-664-2 impacts pubertal development in a precocious-puberty rat model through targeting the NMDA receptor-1†. Issue 6 (27th March 2019) - Ju, Minda; Yang, Liu; Zhu, Jing; Chen, Zhejun; Zhang, Mizhen; Yu, Jin; Tian, Zhanzhuang
Abstract: Precocious puberty (PP) commonly results from premature activation of the hypothalamic–pituitary–gonadal axis (HPGA). Gonadotropin-releasing hormone (GnRH) is the initial trigger for HPGA activation and plays an important role in puberty onset. N-methyl-D-aspartate (NMDA) can promote pulsatile GnRH secretion and accelerates puberty onset. However, the mechanism of N-methyl-D-aspartate receptors (NMDARs) in PP pathogenesis remains obscure. We found that serum GnRH, luteinizing hormone (LH), follicle-stimulating hormone (FSH), estrogen (E2 ) levels, hypothalamic NMDAR1, and GnRH mRNA expression peaked at the vaginal opening (VO) day. Next, the hypothalamic NMDAR1 mRNA and protein levels in rats treated with danazol, a chemical commonly effecting on the reproductive system, were significantly increased at the VO day (postnatal day 24) compared to controls, accompanied by enhanced serum GnRH, LH, FSH, and E2 levels. Further, microRNA-664-2 (miR-664-2) was selected after bioinformatics analysis and approved in primary hypothalamic neurons, which binds to the 3′-untranslated regions of NMDAR1. Consistently, the miR-664-2 expression in hypothalamus of the Danazol group was decreased compared to Vehicle. Our results suggested that attenuated miR-664-2 might participate in PP pathogenesis through enhancing the NMDAR1 signaling. Abstract : Increased hypothalamic NMDAR1 expression correlates to precocious puberty. MiR-664-2 regulates precocious puberty onset. MiR-664-2 targets NMDAR1 and modulates the HPGA activity.